PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR BASIC MATERIALS DAN ENERGY Di ASEAN TAHUN 2022-2024 - Firda Iffatus Suroyya; Mariana Mariana (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to examine the impact of Enviromental, Social, and Governance (ESG) factors on financial performance, with Debt to Asset ratio (DAR) serving as a moderating variable. The research employs a quantitative approach using EViews 13 software, and data anaysis is conducted via panel data regression. The study utilitizes a sample of parent companies operating in the Basic Materials and Energy sectors in ASEAN from 2022 to 2024. The results of the study indicate that the Environmental variable has a significant negative effect on financial performance, as proxied by return on Assets (ROA). Meanwhile, the Social and Governance variables do not have a significant effect on the company's financial performance. Simultaneously, ESG variables have a significant effect on a company's financial performance. Additionally, the debt-to-asset ratio (DAR), as a control variable, has a positive and significant effect on the company's financial performance. Keywords: Environmental, Social, Governance, Financial Performance, Debt to Asset ratio (DAR)